(untitled) (Global Journal of Science Frontier Research, 2016)
In the atmospheric boundary layer there are horizontal pressure gradient and Coriolis force to the velocity distribution signify that, the horizontal component of the velocity in the boundary layer turns left (right) with increasing height in the Southern (Northern) Hemisphere, downward (upward) motion occurs on the windward (lee) side of the mountain, and downward (upward) motion also occurs on the slope to the right (left) of the geostrophic wind in the Northern Hemisphere, whereas in the Southern Hemisphere upward (downward) motion occurs on the slope to the left (right) of the geostrophic wind. Using Navier-Stokes equations for threedimensional stationary flows, hydrostatic and continuity equations, the effects of first order reactant of Coriolis force and dust particles for small Reynolds number in the atmospheric boundary layer over territory is obtained.